Brillouin fiber laser with significantly reduced gain medium length operating in L-band region - Shahi, Sharifeh; Harun, Sulaiman Wadi; Dimyati, Kaharudin; Ahmad, Harith (Electromagnetics Academy, 2009)
Brillouin fiber laser (BFL) is demonstrated using a piece of photonic crystal fiber (PCF) in conjunction with a Bismuth-based erbium-doped fiber (Bi-EDF) as the gain media with a simple ring resonator. The proposed BFL operates at wavelength of 1574.08 nm, which is 0.08 nm shifted from the Brillouin pump wavelength with a maximum peak power of 8dBm. The BFL has a side mode suppression ratio and 3dB bandwidth of approximately 23 dB and 0.02 nm respectively limited by the optical spectrum analyzer resolution. The BFL is also stable at room temperature and compact due to the use of only 20 m long of PCF and 215 cm long of Bi-EDF.